Conditions in home and transplant soils have differential effects on the performance of diploid and allotetraploid anthericum species - Černá, Lucie; Münzbergová, Zuzana (PloS one, 2015)
Due to increased levels of heterozygosity, polyploids are expected to have a greater ability to adapt to different environments than their diploid ancestors. While this theoretical pattern has been suggested repeatedly, studies comparing adaptability to changing conditions in diploids and polyploids are rare. The aim of the study was to determine the importance of environmental conditions of origin as well as target conditions on performance of two Anthericum species, allotetraploid A. liliago and diploid A. ramosum and to explore whether the two species differ in the ability to adapt to these environmental conditions. Specifically, we performed a common garden experiment using soil from 6 localities within the species' natural range, and we simulated the forest and open environments in which they might occur. We compared the performance of diploid A. ramosum and allotetraploid A. liliago originating from different locations in the different soils. The performance of the two species was not affected by simulated shading but differed strongly between the different target soils. Growth of the tetraploids was not affected by the origin of the plants. In contrast, diploids from the most nutrient poor soil performed best in the richest soil, indicating that diploids from deprived environments have an increased ability to acquire nutrients when available. They are thus able to profit from transfer to novel nutrient rich environments. Therefore, the results of the study did not support the general expectation that the polyploids should have a greater ability than the diploids to adapt to a wide range of conditions. In contrast, the results are in line with the observation that diploids occupy a wider range of environments than the allotetraploids in our system.
Keywords: fyziologická adaptace; liliovité; Ecosystem; diploidie; Liliaceae; půda; Soil; polyploidie; Polyploidy; Diploidy; ekosystém; Adaptation, Physiological